0
$\begingroup$

Let $R$ be a unital commutative ring and $m_1,m_2$ distinct maximal ideals. Prove that $$\frac{R}{m_1m_2}\simeq\frac{R}{m_1} \times \frac{R}{m_2}.$$

I think something like this homomorphism might work: $\phi(r)=(r+m_1,r+m_2)$.

Now $\ker\phi=\cdots=m_1\cap m_2$, but it's not clear if it is a surjection.

Also it's true that

If $m_1,m_2$ are maximal ideals of $R$, then $m_1m_2=m_1\cap m_2$.

$\endgroup$
  • $\begingroup$ Chinese remainder theorem in generalized form. $\endgroup$ – egreg Dec 28 '13 at 20:56
  • 1
    $\begingroup$ Note the statement here en.wikipedia.org/wiki/… that if the ideals $m_i$ are pairwise coprime (meaning $m_ + m_j = R$ for $i \ne j$, which holds if they are maximal) then their produtc coincides with their intersection. $\endgroup$ – Andreas Caranti Dec 28 '13 at 22:17
2
$\begingroup$

The map $\phi : R \to \frac{R}{m_1}\times \frac{R}{m_2}$, $\phi(r) = (r + m_1, r + m_2)$ is the correct homomorphism to consider.

As $m_1$ and $m_2$ are comaximal, $m_1 + m_2 = R$. As $R$ is unital $1 \in R$. So there are $a\in m_1$, $b \in m_2$ such that $a + b = 1$.

Exercise: Show that $\phi(a) = (0 + m_1, 1 + m_2)$ and $\phi(b) = (1 + m_1, 0 + m_2)$.

We have $\phi(a) = (a + m_1, a + m_2) = (0 + m_1, 1 - b + m_2) = (0 + m_1, 1 + m_2)$. Likewise for $\phi(b)$.

Now, any $(r_1 + m_1, r_2 + m_2) \in \frac{R}{m_1}\times\frac{R}{m_2}$ can be written as a linear combination of $\phi(a)$ and $\phi(b)$.

Exercise Show that there is $x \in R$ such that $\phi(x) = (r_1 + m_1, r_2 + m_2)$.

We have $(r_1 + m_1, r_2 + m_2) = (r_1 + m_1, 0 + m_2) + (0 + m_1, r_2 + m_2) = r_1\phi(a) + r_2\phi(b)$ so if we set $x = r_1a+r_2b$, we see that $\phi(x) = (r_1 + m_1, r_2 + m_2)$.

So the map $\phi$ is surjective, so by the first isomorphism theorem

$$\frac{R}{\ker\phi} \cong \frac{R}{m_1}\times\frac{R}{m_2}.$$

As you've already determined, $\ker\phi = m_1\cap m_2$. As $m_2$ is an ideal, $Rm_2 \subseteq m_2$, so $m_1m_2 \subseteq m_2$. Likewise, $m_1m_2 \subseteq m_1$ so $m_1m_2 \subseteq m_1\cap m_2$.

Exercise: Show $m_1\cap m_2 \subseteq m_1m_2$. Hint, use the fact that we have $a \in m_1$ and $b \in m_2$ such that $a + b = 1$, then pick $r \in m_1\cap m_2$.

As $a + b = 1$, $ra + rb = r$. As $r \in m_1\cap m_2 \subseteq m_2$ and $a \in m_1$, $ra \in m_1m_2$. Likewise, $rb \in m_1m_2$, so $r = ra + rb \in m_1m_2$.

Then $m_1\cap m_2 = m_1m_2$ so we finally obtain $$\frac{R}{m_1m_2} \cong \frac{R}{m_1}\times\frac{R}{m_2}.$$

$\endgroup$
  • $\begingroup$ If you are stuck on an exercise, you can put your mouse over the grey box beneath it to reveal the solution. I recommend you try the exercises yourself first. $\endgroup$ – Michael Albanese Dec 28 '13 at 23:30
1
$\begingroup$

The fact that $m_1\cap m_2=m_1m_2$ when $m_1\ne m_2$ is really easy to prove. Now the morphism $$ R\to \frac{R}{m_1}\times\frac{R}{m_2} $$ defined by $f(r)=(r+m_1,r+m_2)$ is surjective because $m_1+m_2=R$, so you can write $1=x+y$, with $x\in m_1$ and $y\in m_2$.

If $a,b\in R$, we need to find $r\in R$ such that $r-a\in m_1$ and $r-b\in m_2$. But $$ a-b=(a-b)1=(a-b)x+(a-b)y $$ so $$ r=a-(a-b)x=b+(a-b)y $$ is the element we're looking for.

The kernel of the above morphism is obviously $m_1\cap m_2=m_1m_2$.

Nothing really different from the well known Chinese Remainder Theorem.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.